Barney's fearless penguin - Falconer, Keith R.; Buttfield, Nick (Macmillan Education Australia South Yarra [Vic.], 1999)
"Barney's Fearless Penguin" is a children's story about Barney, a brave penguin who embarks on exciting adventures despite being small and underestimated by others. Throughout the story, Barney faces various challenges in the icy wilderness but overcomes them with courage, cleverness, and determination. The tale emphasizes themes of bravery, self-confidence, and the power of believing in oneself, making it an inspiring read for young audiences who learn that even the smallest individuals can achieve great things with fearlessness and a positive attitude.